2022
DOI: 10.3390/plants11050670
|View full text |Cite
|
Sign up to set email alerts
|

MaxEnt Modeling to Predict the Current and Future Distribution of Pomatosace filicula under Climate Change Scenarios on the Qinghai–Tibet Plateau

Abstract: As an important Tibetan medicine and a secondary protected plant in China, Pomatosace filicula is endemic to the country and is mainly distributed in the Qinghai–Tibet Plateau (QTP). However, global climate change caused by greenhouse gas emissions might lead to the extinction of P. filicula. To understand the potential spatial distribution of P. filicula in future global warming scenarios, we used the MaxEnt model to simulate changes in its suitable habitat that would occur by 2050 and 2070 using four represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 52 publications
(62 reference statements)
4
12
0
Order By: Relevance
“…Based on our results, K. odoratissima grows in heights of 2450 to 3000 m within the region of study. Researchers have reported that the optimum altitude for Pomatosace filicula was 4000–4500 m [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our results, K. odoratissima grows in heights of 2450 to 3000 m within the region of study. Researchers have reported that the optimum altitude for Pomatosace filicula was 4000–4500 m [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in arid and semi-arid ecosystems, studies show that soil properties play an important role in the distribution of plant species [ 37 ]. Previous studies reveal that some plant species can move to higher elevations or latitudes in response to a warming climate [ 28 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The MaxEnt method (Phillips et al, 2004) has proved to be the most effective of the many algorithms for modelling species distribution and for predicting range dynamics under the global climate change (Marcer et al, 2013). The maximum entropy model (MaxEnt) was used in this study (www.cs.princeton.edu/wschapire/MaxEnt), because it has been shown to perform better for modelling the spatial distribution of species in the present and for predicting future changes under the influence of the global climate change (Chen et al, 2022). MaxEnt (Phillips et al, 2004) and uses presence-only data to predict species distributions based on maximum entropy theory.…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, the MaxEnt model is superior to other models when the available sample size is limited (Schmidt et al, 2020;Zeng et al, 2016). For example, Chen et al (2022) used the MaxEnt model to predict the distribution of Pomatosace filicula on the Qinghai-Tibet Plateau under climate change. Their findings showed that future climate change will increase the risk posed to the survival of this species, whose habitat will be reduced further and degraded (Chen et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Chen et al (2022) used the MaxEnt model to predict the distribution of Pomatosace filicula on the Qinghai-Tibet Plateau under climate change. Their findings showed that future climate change will increase the risk posed to the survival of this species, whose habitat will be reduced further and degraded (Chen et al, 2022). Using the MaxEnt model, Zhang et al (2022) were able to identify and locate suitable habitats of Wolfiporia cocos distributed mainly in China's Yunnan Province.…”
Section: Introductionmentioning
confidence: 99%